On the Dynamics of Interest Group Formation and Endogenous Policymaking - Vjollca Sadiraj; Jan Tuinstra; Frans A.A.M. van Winden (Tinbergen Institute, 2000)
We present a dynamic model of the interaction between interest groupsand policymakers, featuringendogenous interest group formation. We show that complicated dynamicpatterns in economicpolicies may arise once interest group formation is taken intoaccount.
Keywords: D23; D72; D78; E32; H30; 330; Interest groups; Aspiration level; Endogenous fluctuations; Interessenvertretung; Politik; Theorie